2019
DOI: 10.1055/s-0039-1697625
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method to Reduce the Incidence of Cyclops Lesion after Anterior Cruciate Ligament Reconstruction

Abstract: The purpose of this study is to determine the influence of debridement in and around the bone tunnels on the prevalence of cyclops lesion (CL), after anterior cruciate ligament reconstruction (ACLR) with hamstring grafts. Our hypothesis was that bone tunnel debridement during ACLR would reduce the prevalence of CL. Methods for debridement in and around the bone tunnels after tunnel drilling were standardized and applied to 38 knees undergoing double-bundle ACLR between 2011 and 2014, Group A (debridement group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…The cause of the nodule in ACL ruptures was thought to be avulsion of pieces of bone from the tibial attachment site of the ACL. 23 Cyclops lesion has also been reported after partial avulsion of small bone pieces from proximal attachment on the femur. 35 Persistent loss of knee extension for more than 2 months even after aggressive rehabilitation after ACL rupture should raise suspicion of a cyclops lesion.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The cause of the nodule in ACL ruptures was thought to be avulsion of pieces of bone from the tibial attachment site of the ACL. 23 Cyclops lesion has also been reported after partial avulsion of small bone pieces from proximal attachment on the femur. 35 Persistent loss of knee extension for more than 2 months even after aggressive rehabilitation after ACL rupture should raise suspicion of a cyclops lesion.…”
Section: Resultsmentioning
confidence: 95%
“…Recommended strategies to prevent cyclops lesions include the following 2 , 6 : Delaying ACLR until after recovery of ROM Minimally invasive surgery compared with open ACLR Creating less debris by use of a sequential reamer and thorough removal of debris Correct tunnel positioning Debridement in and around the bone tunnel 23 Trial extension with the reamer or drill placed through the tibial tunnel to check whether it impinges with the notch Notchplasty if associated with impingement of the ACL graft If possible, drawing the graft from the femoral tunnel first into the tibial tunnel to draw debris into the tibial tunnel Early postoperative mobilization For cyclops lesion associated with bicruciate-retaining arthroplasty, selective fiber releases of the ACL, rounding of the edges of the tibial bone island, and notchplasty 18 …”
Section: Resultsmentioning
confidence: 99%
“…This means that transtibial have more posteriorly placed tibial tunnels than anteromedial portal ACL-R, leading to a comparatively lower risk of distal ACL graft impingement and, thus, cyclops lesion formation. Nagira et al observed in a case-control study that complete removal of tibial ACL remnants during ACL-R resulted in significantly fewer patients requiring cyclops lesions removal [14]. However, a cohort study by Bierke et al showed no increased rate of cyclops lesions after remnant preservation [4].…”
Section: Discussionmentioning
confidence: 99%
“…3 Although recent detailed studies of the ACL functional anatomy have contributed to improved ACLR in which the graft is placed in an anatomic position, the incidence of GRI is still reported to range from 2.2% to 27.3%, as identified during the second-look arthroscopy. 23,24,35,37 A narrowed notch width has been associated with greater risk of ACL graft impingement after ACLR. 13,17,39 In this study, although notchplasty was performed if necessary during primary ACLR, GRI could still be detected during the second-look arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanical block attributed to fibrous tissue originating from drilling debris of the tibial tunnel or the preserved tibial ACL remnant during ACLR has been suggested to cause GRI. 23,24 Clinically, GRI can compromise the outcomes of ACLR, causing effusions, extension deficits, recurrent instability, or anterior knee pain. 3 Although recent detailed studies of the ACL functional anatomy have contributed to improved ACLR in which the graft is placed in an anatomic position, the incidence of GRI is still reported to range from 2.2% to 27.3%, as identified during the second-look arthroscopy.…”
Section: Discussionmentioning
confidence: 99%